1998
DOI: 10.1007/s004320050175
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hypoxia-inducible genes in tumor cells

Abstract: Tumor tissue oxygenation impacts on proliferation of cancer cells and their sensitivity towards radio- and chemotherapy. Under low oxygen, mammalian cells show an adaptive response that leads to the induction of a number of genes with well-defined roles in oxygen supply and energy maintenance, e.g. genes encoding enzymes of the glycolytic pathway. The hypoxia-inducible factor 1 (HIF-1), a transcription factor consisting of the two proteins HIF-1alpha and HIF-1beta, plays a major role in the pleiotropic respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 29 publications
0
45
0
1
Order By: Relevance
“…To study the relationship between TWIST1 and hypoxia, we investigated the expression of TWIST1 mRNA in human cell lines after exposure to hypoxia using a TWIST1-specific TaqMan assay. In cervix carcinoma cells (HeLa), prostate cancer cells (PC3) and colon cancer cells (HCT116), TWIST1 expression was induced four-to eightfold after 24 h of hypoxia (Figures 3a-c) concurrent with PGK1 induction, a validated HIF target (Kress et al, 1998). In contrast, we could not detect significant TWIST1 induction in human embryonic kidney cells (HEK293T) (Figure 3d).…”
Section: Twist1 Is a Target Of Hif-2a Eh Gort Et Almentioning
confidence: 84%
“…To study the relationship between TWIST1 and hypoxia, we investigated the expression of TWIST1 mRNA in human cell lines after exposure to hypoxia using a TWIST1-specific TaqMan assay. In cervix carcinoma cells (HeLa), prostate cancer cells (PC3) and colon cancer cells (HCT116), TWIST1 expression was induced four-to eightfold after 24 h of hypoxia (Figures 3a-c) concurrent with PGK1 induction, a validated HIF target (Kress et al, 1998). In contrast, we could not detect significant TWIST1 induction in human embryonic kidney cells (HEK293T) (Figure 3d).…”
Section: Twist1 Is a Target Of Hif-2a Eh Gort Et Almentioning
confidence: 84%
“…Tsutsumi et al (1988) isolated and sequenced two overlapping clones covering the entire coding sequence of PKM2. Kress et al (1998) indicated that mRNA level of PKM2 is increased in human colorectal cancers in comparison to the corresponding normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of the M2-PK isoenzyme can be caused by mutations in the ras gene and upregulation of HIF-1 (Kress et al, 1998;Mazurek et al, 2001). HIF-1 is stabilised by p53 mutations (Kress et al, 1998;Ravi et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1 is stabilised by p53 mutations (Kress et al, 1998;Ravi et al, 2000). Indeed, mutations in the ras oncogene and p53 antioncogene are detectable in 40 -60% of colorectal cancers (Bos, 1989;Kinzler and Vogelstein, 1996;Dong et al, 2001;Rengucci et al, 2001;Nishikawa et al, 2002;Smith et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation